Tiktok sebagai Mesin Viralitas: Studi Tren Boost Juice di Kalangan Gen Z Jabodetabek - Indri Anggraini; Prima Mulyasari Agustini (Masyarakat Ekonomi Syariah Bogor, 2025)
The phenomenon of virality on social media has reshaped consumer behavior, particularly among Generation Z. This study examines how TikTok, as a short-video platform, influences the perception and purchase interest of Gen Z toward Boost Juice products in the Greater Jakarta area. Using a qualitative case study approach, data were collected through open-ended questionnaires, netnographic observation of TikTok content, and interviews with brand representatives. The findings reveal that organically viral content, combined with the power of digital communities and the Fear of Missing Out (FOMO), drives curiosity and impulsive purchase decisions. Visually engaging content, emotional testimonials from local creators, and community involvement in the “jus ayaya” narrative are key triggers in forming purchase interest. These results affirm TikTok’s role not only as an entertainment platform but also as a strategic medium in shaping digital consumption patterns and generating impactful marketing momentum. The study recommends brands to adopt adaptive strategies and leverage authentic content to navigate the dynamics of digital virality.